2017
DOI: 10.3232/gcg.2017.v11.n2.01
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Innovation Performance Between Foreign Subsidiaries and Owned Domestic Firms in Colombian Manufacturing Sector

Abstract: This paper analyzes the innovation performance of foreign subsidiaries compared to domestic owned firms using a firm level dataset of Colombian manufacturing firms. The results show that foreign subsidiaries are superior in knowledge production over domestic firms and this superiority is because they make a more intensive use of internal and external knowledge inputs. However, when foreign subsidiaries are compared with national exporting companies the gaps in innovation performance is not as wide. Our finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Enterprises that operate not only in the country, but also abroad, show a greater propensity to conduct innovative activity compared to entities operating on regional or national markets. There are several studies that confirm the fact that there is a positive relation between the presence of a company on foreign markets and the level and growth of its technological knowledge, e.g., [53,54]. Researchers agree that increased pressure from competitors in international markets is forcing companies to improve their products and adapt to new market conditions.…”
Section: H1d Sme That Had Randd Cooperation Is More Likely To Have Or...mentioning
confidence: 99%
“…Enterprises that operate not only in the country, but also abroad, show a greater propensity to conduct innovative activity compared to entities operating on regional or national markets. There are several studies that confirm the fact that there is a positive relation between the presence of a company on foreign markets and the level and growth of its technological knowledge, e.g., [53,54]. Researchers agree that increased pressure from competitors in international markets is forcing companies to improve their products and adapt to new market conditions.…”
Section: H1d Sme That Had Randd Cooperation Is More Likely To Have Or...mentioning
confidence: 99%
“…Although many technological activities continue to be located at home, MNEs have evolved toward less hierarchical organizational structures that are based on integrated technology Two-way FDI knowledge spillovers networks, which allows them to more efficiently coordinate their diversified and geographically dispersed innovation activities and capacities, both within the organization and with other actors on a global scale (Hedlund, 1994;Cantwell, 1995;Iammarino and McCann, 2013;Perri et al, 2017). Several studies have thus found a variety of patterns of innovative activities in foreign subsidiaries, observable both in developed countries (Florida, 1997;Cantwell and Mudambi, 2005;Alvarez and Cantwell, 2011;Achcaoucaou et al, 2017) and in the developing world (Hobday and Rush, 2007;Albis and Alvarez, 2017;Galina et al, 2011;Hansen et al, 2020;Marin and Bell, 2010). This stream of literature finds that technologically active subsidiaries abroad generate new knowledge beyond an MNE's headquarters, contributing significantly to the MNE's overall competitive advantages.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Several studies have thus found a variety of patterns of innovative activities in foreign subsidiaries, observable both in developed countries (Florida, 1997; Cantwell and Mudambi, 2005; Álvarez and Cantwell, 2011; Achcaoucaou et al. , 2017) and in the developing world (Hobday and Rush, 2007; Albis and Álvarez, 2017; Galina et al. , 2011; Hansen et al.…”
Section: Theory and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation